Peran Notaris dalam Memberikan Penyuluhan Hukum untuk Memenuhi Asas Proporsionalitas dalam Akta Para Pihak - Fitra Yesi (Faculty of Law Universitas Islam Indonesia, 2023)
Notaries have the authority to provide legal advice on the parties’ deeds or partij acta. However, it is not uncommon for the principle of proportionality to be unfulfilled in the deed to cause problems in the future, leading to the annulment of the deed by the court. This is the result of legal counseling that was not adopted by the parties. The formulation of the problem in this research is what is the role of the Notary in providing legal advices so that the principle of proportionality is fulfilled in making deeds of the parties, and what is the responsibility of the Notary whose deed does not satisfy the principle of proportionality and is thus annulled by the Court. This is a normative legal research carried out by using statutory and conceptual approaches. The results of the research and discussion show that the role of the Notary in providing legal counseling is only limited to the authority of the Notary and does not create obligations for the parties. As a result of this authority, the principle of proportionality will be difficult to fulfill even if the deed is made in authentic form and is a deed of the parties. The notary cannot be responsible for the annulment of the deed by the Court because the principle of proportionality is not fulfilled. As failure to meet the principle of proportionality is not part of the Notary’s responsibility which is regulated through statutory regulations. However, morally a Notary can fulfill the principle of proportionality through an authority, namely legal counselingKey Word: Notary, Proportionality, Deed of the Parties AbstrakNotaris memiliki kewenangan untuk memberikan penyuluhan hukum terhadap akta para pihak atau partij acta. Namun, tidak jarang asas proporsionalitas yang tidak dipenuhi dalam akta tersebut dapat menimbulkan permasalahan dikemudian hari hingga berujung pada pembatalan akta oleh pengadilan. Hal ini akibat dari penyuluhan hukum yang tidak diikuti oleh para pihak. Rumusan masalah dalam penelitian ini yaitu bagaimana peran Notaris dalam memberikan penyuluhan hukum agar terpenuhinya asas proporsionalitas dalam pembuatan akta para pihak, dan bagaimana tanggung jawab Notaris yang aktanya tidak memenuhi asas proporsionalutas dan dibatalkan oleh Pengadilan. Penelitian ini merupakan penelitian hukum normatif yang dilakukan dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian dan pembahasan menunjukkan bahwa Peran Notaris dalam memberikan penyuluhan hukum hanya sebatas kewenangan bagi Notaris dan tidak melahirkan kewajiban bagi para pihak. Akibat dari kewenangan tersebut, asas proporsionalitas akan sulit dipenuhi walaupun akta dibuat dalam bentuk otentik dan merupakan akta para pihak. Notaris tidak dapat bertanggung jawab atas dibatalkannya akta oleh Pengadilan karena asas proporsionalitas yang tidak terpenuhi. Sebagaimana tidak terpenuhinya asas proporsionalitas bukan merupakan sebuah tanggung jawab Notaris yang diatur melalui peraturan perundang-undangan. Namun, secara moralitas Notaris dapat memenuhi asas proporsionalitas melalui sebuah kewenangan yaitu penyuluhan hukum.Kata-kata Kunci: Notaris, Proporsionalitas, Akta Para Pihak